An eight-armed Natya Ganapati - Mumbai Archive Project Team (Jio Institute, 2024)
Saraswati Nakhva’s father’s fishing net once ensnared a wooden Ganesha from the sea. It depicts an eight-armed Natya Ganapati in a dancing posture, surrounded by smaller figures. The Nakhva house now proudly displays the cleaned and restored carving on its wall.